The Impact of Culture on Loss Aversion. (5th February 2016) - Wang, Mei; Rieger, Marc Oliver; Hens, Thorsten
Abstract: Based on the literature on the relationship between culture, emotion, and loss aversion, we derive that culture can influence the degree of loss aversion. To test our hypotheses, we conduct a standardized survey in 53 countries worldwide that includes the questions from the Hofstede survey on cultural dimensions as well as lottery questions on loss aversion. The results show that individualism, power distance, and masculinity increase loss aversion as predicted, whereas the impact of uncertainty avoidance is less significant. Moreover, we also find a relation between the distribution of major religions in a country and loss aversion. In comparison, the connection of loss aversion to macroeconomic variables seems to be much smaller. Copyright © 2016 John Wiley & Sons, Ltd.